English fairy and other folk tales - Hartland, Edwin Sidney, 1848-1927 (Detroit : Singing Tree Press, 1968)
A collection of traditional English tales about legendary people and events, fairies, giants, witches, goblins, and ghosts
Bibliographical footnotes
Keywords: Tales -- England; Fairy tales, English